2020
DOI: 10.1016/j.diabres.2020.108286
|View full text |Cite
|
Sign up to set email alerts
|

Well-controlled vs poorly-controlled diabetes in patients with COVID-19: Are there any differences in outcomes and imaging findings?

Abstract: We aimed to compare the clinical outcomes and imaging findings between COVID-19 patients with well-controlled diabetes and those with poorly-controlled diabetes. Methods: In this retrospective single-center study, 117 patients with coexistent COVID-19 and type 2 diabetes mellitus were included. Patients were divided into two groups based on HbA1c values. Clinical data and laboratory parameters were collected from patients' medical records. Also, the chest computed tomography (CT) score was defined by the summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 46 publications
6
45
2
11
Order By: Relevance
“…As mentioned earlier, our study showed that proteinuria was an independent risk factor for AKI development among patients with diabetes and COVID-19; this finding supports previous studies underlining the strict relationship between albumin excretion rate and cardiorenal outcomes in diabetic nephropathy [ 26 28 ]. Furthermore, while no association was previously found between HBA1c level and mortality in patients with coexistent diabetes and COVID-19 [ 29 , 30 ], this study showed that higher HBA1c levels put patients with diabetes at greater risk of developing AKI during hospital stay.…”
Section: Discussioncontrasting
confidence: 88%
“…As mentioned earlier, our study showed that proteinuria was an independent risk factor for AKI development among patients with diabetes and COVID-19; this finding supports previous studies underlining the strict relationship between albumin excretion rate and cardiorenal outcomes in diabetic nephropathy [ 26 28 ]. Furthermore, while no association was previously found between HBA1c level and mortality in patients with coexistent diabetes and COVID-19 [ 29 , 30 ], this study showed that higher HBA1c levels put patients with diabetes at greater risk of developing AKI during hospital stay.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies have shown that severe cases of COVID-19 may develop acute respiratory distress syndrome (ARDS), multiple organ failure, and ultimately succumb to death [ 2 , 3 ]. Among patients with COVID-19, older individuals, male patients, and those with comorbidities are known to have higher morbidity and mortality rates [ 4 , 5 ][ 38 ]. Respiratory failure seems to be the main cause of death in infected patients [ 6 ]; identification of the exact mechanism of death, however, can only be achieved after performing pathologic examination on decedents.…”
Section: Introductionmentioning
confidence: 99%
“…In an Iranian hospital, 24 persons with HbA1c 6.5-7 had a similar mortality rate (21%) to that of 93 persons (23%) with HbA1c 8%-11.2%. 4 In analysis of 1317 persons with diabetes hospitalized for COVID-19 in France, the outcome of tracheal intubation or death by day 7 was not associated with HbA1c level on admission, although there was a linear correlation with admission plasma glucose, as well as with body mass index. 5 Another study, of 1279 persons with diabetes hospitalized for COVID-19 in New York, showed no association of mortality with HbA1c on admission, whereas obesity, as well as increasing age and male sex and increasing complexity of outpatient diabetes treatment, were again associated with greater likelihood of adverse outcome.…”
mentioning
confidence: 96%